Causal Effect of Blood Pressure on Bone Mineral Density and Fracture: A Mendelian Randomization Study - He, Bin; Yin, Lifeng; Zhang, Muzi; Lyu, Qiong; Quan, Zhengxue; Ou, Yunsheng (Frontiers in Endocrinology, 2021)
Background Hypertension may have some association with osteoporosis. This Mendelian randomization (MR) study aimed to explore the causal effect of blood pressure (BP) on bone mineral density (BMD), fall and fracture. Methods We used the genome-wide association study (GWAS) summary data among 330,956 European-descent individuals to identify 107 single-nucleotide polymorphisms (SNPs) as the instrumental variables of BP. MR analyses of these instruments were performed on 53,236 European individuals for the association with forearm BMD (FA-BMD), femoral neck BMD (FN-BMD) and lumbar spine BMD (LS-BMD), 451,179 European individuals for fall susceptibility and 426,824 individuals from European descent for fracture. Conventional inverse variance weighted (IVW) method was adopted to obtain the causal estimates of BP on different outcomes, while weighted median, MR-egger and MR pleiotropy residual sum and outlier (MR-PRESSO) test were used for sensitivity analyses. Results Genetically high pulse pressure (PP) could significantly improve FA-BMD (beta-estimate: 0.038, 95% conﬁdence interval [CI]: 0.013 to 0.063, SE:0.013, P-value=0.003